2018
DOI: 10.1186/s12889-018-6296-6
|View full text |Cite
|
Sign up to set email alerts
|

Current and ceased users of sit stand workstations: a qualitative evaluation of ergonomics, safety and health factors within a workplace setting

Abstract: BackgroundMany workplaces have implemented sit-stand workstations (SSW), which enable a worker to transition between sitting and standing as they perform their work activities. The factors which determine the initial adoption, sustainability or cessation of use for a SSW, remain largely unexamined. This study investigates the experiences of workers who had previously used or were currently using a SSW.MethodsThe study setting was within an Australian university. Participants who were current or past SSW users,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…The present trial likewise indicated the greatest intervention effects were observed early in the day, but unlike the pilot study, did not see any specific effects around midday, and saw a clear trend of diminishing effects over time (both by subjective time and clock time). The diminished effects, evident towards the end of the day, may be related to workers experiencing fatigue or muscle discomfort, which is consistent with qualitative research identifying a preference for standing in the morning, and a decline in standing as the day progressed [14]. This timing may also be related to when tasks are undertaken (for example, standing when checking emails at the start of the day).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The present trial likewise indicated the greatest intervention effects were observed early in the day, but unlike the pilot study, did not see any specific effects around midday, and saw a clear trend of diminishing effects over time (both by subjective time and clock time). The diminished effects, evident towards the end of the day, may be related to workers experiencing fatigue or muscle discomfort, which is consistent with qualitative research identifying a preference for standing in the morning, and a decline in standing as the day progressed [14]. This timing may also be related to when tasks are undertaken (for example, standing when checking emails at the start of the day).…”
Section: Discussionsupporting
confidence: 74%
“…This timing may also be related to when tasks are undertaken (for example, standing when checking emails at the start of the day). Within the qualitative study, many workers also reported factors relating to comfort or fatigue as contributing to their sitting later in the working day [14]. There is also preliminary evidence that the work environment may impact on breaks in sitting time [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest that there are minimum design requirements to enable workers to complete their work, however, beyond this employees engage their reflexivity to choose whether and how to respond to the sit-stand desk, whilst their choices are disposed by various structural factors that enable or impede use of the sit-stand desk [39]. The finding that some employees were willing to adapt how they work to accommodate the sit-stand desk, and some were not, is consistent with a recent qualitative study of current and past sit-stand desk users [40]. Organisations should consider models of sit-stand desks that suit their environment, and permit employees to trial and select models of sit-stand desk that best ‘fit’ their own needs and how they interact with their desk, to minimise the amount of adjustment required.…”
Section: Discussionsupporting
confidence: 63%
“…A recent study, which included interviews with current and previous users of sit-stand workstations, showed that sustained use of the furniture was dependent on personal considerations, such as the selection of a specific work task while using the standing option [ 34 ]. Although the inclusion of previous users added an additional perspective, previous users had all specifically requested to have a sit-stand workstation in the past, indicating similar levels of enthusiasm as the current users.…”
Section: Introductionmentioning
confidence: 99%